Pengaruh Motivasi dan Kepemimpinan terhadap Kinerja - Ririn Andriana (Universitas Proklamasi 45 Yogyakarta, 2015)
This study aims to examine and analyze the influence of motivation and leadership on the performance of the Sales Promotion Merchandising (SPM) Suntory Beverage Garuda Indonesia Sidoarjo. In this study, using a motivational variable (X1), leadership (X2) and performance (Y). Data collected through questionnaires and conducted on 30 Sales Promotion Merchandising (SPM) PT. Suntory Garuda Beverage Sidoarjo. Analysis of the data in this study using SPSS version 14, engineering test data used in this study include test validity by factor analysis, reliability testing with ALPHA Cronvbach, classic assumption test and multiple linear regression analysis, to test and prove the research hypothesis. In this study all theories, independent and dependent variables are accepted and valid. In this study proves that the motivation partially have a positive influence on employee performance, with significance 0.004. Similarly, for the leadership also have a positive influence on employee performance, with significance 0.002